2022
DOI: 10.3389/fimmu.2022.997240
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in metabolites of the kynurenine pathway in Alzheimer’s disease, Parkinson’s disease, and Huntington’s disease: A systematic Review and meta-analysis

Abstract: BackgroundTryptophan (TRP) is an essential amino acid that must be provided in the diet. The kynurenine pathway (KP) is the main route of TRP catabolism into nicotinamide adenosine dinucleotide (NAD+), and metabolites of this pathway may have protective or degenerative effects on the nervous system. Thus, the KP may be involved in neurodegenerative diseases.ObjectivesThe purpose of this systematic review and meta-analysis is to assess the changes in KP metabolites such as TRP, kynurenine (KYN), kynurenic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 110 publications
2
17
0
Order By: Relevance
“…Past studies investigating concentrations of KA among patients with AD compared to controls have shown increased concentrations in the CSF but lower concentrations of KA in plasma. 22,23,31 Meanwhile, other research has shown reduced concentrations of KA in CSF. Unlike QA, KA in CSF is seldom reported to be increased in neurodegenerative diseases other than AD.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies investigating concentrations of KA among patients with AD compared to controls have shown increased concentrations in the CSF but lower concentrations of KA in plasma. 22,23,31 Meanwhile, other research has shown reduced concentrations of KA in CSF. Unlike QA, KA in CSF is seldom reported to be increased in neurodegenerative diseases other than AD.…”
Section: Discussionmentioning
confidence: 99%
“…With the increase of TC content in serum, the content of LDL, which is the main carrier to promote the absorption and utilization of cholesterol in peripheral tissues, obviously increased, while the content of HDL involved in the reverse transport of total cholesterol decreased due to cholestasis ( Hou et al, 2019 ; Berköz et al, 2021 ). 5-hydroxyindoleacetic acid is produced through the metabolic pathway of 5-HT, which is mainly concentrated in the brain tissue, and has an influence on the toxicity of nerve cells and the transmission of neurotransmitters at the nerve terminals ( Han et al, 2019 ; Zhang et al, 2021 ; Fathi et al, 2022 ). The results showed that, the administration of rhubarb anthraquinone could repair damaged hepatocytes, improve the mitochondrial dysfunction and cholestasis, and enhance the metabolic function of the liver, thus playing a role in protecting the liver.…”
Section: Discussionmentioning
confidence: 99%
“…114,115 KYN then follows a metabolic pathway, also known as the KYN pathway to generate NAD + . 108–113 Such KYN pathways have been reported to modulate dopaminergic, nicotinergic, and glutaminergic neurotransmission, which may be related to numerous psychiatric and neurodegenerative symptoms. 108–113,116…”
Section: Small Molecule-based Neurotransmitters and Their Metal-media...mentioning
confidence: 99%
“…114,115 KYN then follows a metabolic pathway, also known as the KYN pathway to generate NAD + . [108][109][110][111][112][113] Such KYN pathways have been reported to modulate dopaminergic, nicotinergic, and glutaminergic neurotransmission, which may be related to numerous psychiatric and neurodegenerative symptoms. [108][109][110][111][112][113]116 In neurodegeneration, however, the oxidation process of Trp to KYN can be facilitated in the presence of redox-active transition metal ions producing ROS.…”
Section: Tryptophanmentioning
confidence: 99%